2014
DOI: 10.3892/ijo.2014.2752
|View full text |Cite
|
Sign up to set email alerts
|

Dual regulation of receptor tyrosine kinase genes EGFR and c-Met by the tumor-suppressive microRNA-23b/27b cluster in bladder cancer

Abstract: Recent clinical trials of chemotherapeutics for advanced bladder cancer (BC) have shown limited benefits. Therefore, new prognostic markers and more effective treatment strategies are required. One approach to achieve these goals is through the analysis of RNA networks. Our recent studies of microRNA (miRNA) expression signatures revealed that the microRNA-23b/27b (miR-23b/27b) cluster is frequently downregulated in various types of human cancers. However, the functional role of the miR-23b/27b cluster in BC c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 47 publications
2
71
0
Order By: Relevance
“…The expression levels of the miR-23b/27b cluster were significantly reduced in advanced bladder cancer clinical specimens [32]. Luciferase reporter assays and western blotting demonstrated that EGFR and MET transcripts were directly regulated by the miR-23b/27b cluster.…”
Section: Mirnas Targeting Egfrmentioning
confidence: 99%
“…The expression levels of the miR-23b/27b cluster were significantly reduced in advanced bladder cancer clinical specimens [32]. Luciferase reporter assays and western blotting demonstrated that EGFR and MET transcripts were directly regulated by the miR-23b/27b cluster.…”
Section: Mirnas Targeting Egfrmentioning
confidence: 99%
“…MicroRNA‐based therapy has been suggested to be a rational and potential approach for the therapeutic targeting of EGFR . To date, a number of miRNAs, such as miR‐7 , miR‐27b and miR‐133a have been demonstrated to directly target EGFR. However, more anti‐EGFR miRNAs need to be explored, as a single mRNA can be the target of hundreds of miRNAs, and combinations of multiple tumour suppressive miRNAs targeting an individual gene might improve therapeutic efficacy by reducing resistance .…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Decreased epidermal growth factor receptors (EGFRs) and c-Met signaling pathways are responsible for the miR-27b inhibition effect on BC proliferation, invasion, and /or metastasis. EGFR is the cell-surface receptor of the extracellular ligands-EGF family and c-Met is a hepatocyte growth factor (HGF) receptor 19 (Figure 3). …”
Section: Mir-27b Affects Cell Proliferation In Tumormentioning
confidence: 99%
“…9 MiR-27b is a familiarly dysregulated miRNA in human cancers, for example it is always up-regulated in glioma, 10 cervical cancer, 11 breast cancer (BRC) 12 and down-regulated in lung adenocarcinoma, 13,14 prostate cancer (PCa), 15 colorectal cancer (CRC), 16 acute myeloid leukemia (AML), 17 gastric cancer (GC), 18 and bladder cancer (BC). 19 Through the suppression of multiple targets, miR27b has recently emerged as a key suppressor or an oncogene in cancers. Here, we review the role of miR-27b in human cancers and partly reveal its functions in tumor progression, therapy, prognosis, as well as its prospect of clinical application based on molecular targeting therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%